Preparation and characterization of oriented hydroxyapatite bundles in supersaturated solution: ionic interference and charge balance - Wenxi Yan; Shan Zhang; Yinchuan Wang; Guiyong Xiao; Yupeng Lu (Journal of Materials Research and Technology, 2023)
Hydroxyapatite (HA), an artificial bioceramic with high similarity to the mineral constituent of vertebrate bones and teeth, has attracted extensive attention due to its excellent bioactivity and biocompatibility. The micro-nano structure of HA is a vital factor in expanding its application in biomedicine as well as in many other industrial fields. What's more, HA nanofiber exhibits outstanding properties among its various morphologies. In this work, HA bundles with the same oriented nanofibers are successfully synthesized in a solvothermal reaction system by controlling the amount of carbonate addition and using oleic acid as a template. Under the synergistic effect of different molar ratios of hydroxide ion to carbanion ([OH−]/[CO32−]), HA nanofibers gradually increase their aspect ratio and tend to grow into oriented bundles. This product has admirable flexibility and good mechanical strength, as well as great application potential. Based on the characterization and analysis results, we take a further exploration of the effects of ionic interference ([OH−]/[CO32−]) and charge balance (CO32− vs PO43, Na + vs Ca2+) on the microstructure, phase composition and thermal stability of HA nanofibers bundles (HANBs) in the solvothermal system during the chemical reaction process. And then, the formation and assembly mechanism of HANBs is proposed, and the role of van der Waals forces in this process is also discussed. Furthermore, the generation of this clustered state may be influenced by the shift in the dissolution equilibrium of insoluble carbonates during synthesis. This research provides a new direction for controlling the micro-nano morphology of HA to further obtain products with desirable properties.